Evaluation of insertion and deletion polymorphisms of Brazilian Odontoceti - Dafne Adriana Abreu dos Anjos; Anna Luiza dos Santos Donato; Rodrigo Goldenberg-Barbosa; Elizeu Fagundes de Carvalho; Cesar Rogerio Leal do Amaral (Academia Biology)
Brazilian Odontoceti strandings provide substantial information about distribution, health, and genetics of this suborder. Moreover, molecular identification is required and studies in this area have been developed to clarify their distribution and phylogeny, since morphological identification may be infeasible in some degraded samples. In this study, we performed an in silico analysis of InDels in 16S rRNA from 27 species of toothed whales, dolphins, and porpoises present in Brazilian waters and recurrently found stranded in the region. We accomplished the species’ identification based on the unique SpInDel profile for all Odontoceti species, except Phocoenas, and for six species of delphinids.